KAJIAN PENERAPAN ASPEK KESELAMATAN DAN KESEHATAN KERJA PADA PROYEK JALAN TOL XYZ - Girsang, Hamonangan; Amalia, Hani (Fakultas Teknik, Universitas Wiraraja, 2025)
The simultaneous implementation of occupational safety and health (OSH) has a positive and significant impact on accident rates. The higher the level of safety and OSH in the workplace, the lower the rate of workplace accidents. This study is related to the XYZ (Elevated) Toll Road Project, a toll road construction project that connects the Inner City Toll Road. During the execution of this project, an incident occurred in which an excavator operator made an error while operating heavy equipment and touched the MCB in the work area. This incident resulted in material damage and the potential for minor injuries to workers. To identify the key factors influencing OSH implementation in the XYZ (Elevated) Toll Road Project, a survey was conducted using questionnaires provided to staff and workers on the project. The collected data were then analyzed using SPSS software. The results of the research showed that OSH planning factors have a dominant influence on OSH implementation in the XYZ (Elevated) Toll Road Project, with a percentage of 41%.